Comparative Genomics Provide Insights Into Function and Evolution of Odorant Binding Proteins in Cydia pomonella - Huang, Cong; Zhang, Xue; He, Dongfeng; Wu, Qiang; Tang, Rui; Xing, Longsheng; Liu, Wanxue; Wang, Wenkai; Liu, Bo; Xi, Yu; Yang, Nianwan; Wan, Fanghao; et al. (Frontiers in Physiology, 2021)
Insect olfaction is vital for foraging, mating, host-seeking, and avoidance of predators/pathogens. In insects, odorant binding proteins (OBPs) are involved in transporting hydrophobic odor molecules from the external environment to receptor neurons. The codling moth, Cydia pomonella, one of the most destructive insect fruit pests, causes enormous economic losses. However, little is known about the number, variety, gains and losses, and evolution of OBP genes in C. pomonella. Here we report the identification of 40 OBPs in C. pomonella, most (75%) of which are classic OBPs, using genomic and transcriptomic analyses. Two OBP genes were lost in C. pomonella relative to possible distant ancestor in Lepidoptera lineage based on an analysis of gene gains and losses. The phylogenetic tree and chromosome location showed that the expansion of OBP genes mainly resulted from tandem duplications, as the CpomGOBP2 gene was duplicated twice along with loss of CpomPBPB. Two positive selection sites of the CpomGOBP1 gene were identified while other OBP genes evolved under purifying selection. Our results provide fundamental knowledge of OBP genes allowing further study of their function in C. pomonella.